Dynamics of Normalization in the New Middle East: An Analysis of the Abraham Accords and Arab Strategic Interests - Burdah, Ibnu (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
In January 2020, President Donald Trump introduced the Abraham Accords, often hailed as the deal of the century. Many criticized the proposal for focusing solely on U.S. diplomatic peace efforts in the Middle East and shifting the core issue from the Israeli-Palestinian conflict to the normalization of Arab-Israeli relations. Despite its controversies, the Abraham Accords normalized relations between Israel and the United Arab Emirates and Bahrain, potentially reshaping the